A New Immuno‐, Dystrophin‐Deficient Model, the NSG‐mdx4Cv Mouse, Provides Evidence for Functional Improvement Following Allogeneic Satellite Cell Transplantation1. (23rd August 2013) - Arpke, Robert W.; Darabi, Radbod; Mader, Tara L.; Zhang, Yu; Toyama, Akira; Lonetree, Cara‐lin; Nash, Nardina; Lowe, Dawn A.; Perlingeiro, Rita C.R.; Kyba, Michael
Abstract: Transplantation of a myogenic cell population into an immunodeficient recipient is an excellent way of assessing the in vivo muscle‐generating capacity of that cell population. To facilitate both allogeneic and xenogeneic transplantations of muscle‐forming cells in mice, we have developed a novel immunodeficient muscular dystrophy model, the NSG‐mdx 4Cv mouse. The IL2Rg mutation, which is linked to the Dmd gene on the X chromosome, simultaneously depletes NK cells and suppresses thymic lymphomas, issues that limit the utility of the SCID/mdx model. The NSG‐mdx 4Cv mouse presents a muscular dystrophy of similar severity to the conventional mdx mouse. We show that this animal supports robust engraftment of both pig and dog muscle mononuclear cells. The question of whether satellite cells prospectively isolated by flow cytometry can confer a functional benefit upon transplantation has been controversial. Using allogeneic Pax7‐ZsGreen donors and NSG‐mdx 4Cv recipients, we demonstrate definitively that as few as 900 FACS‐isolated satellite cells can provide functional regeneration in vivo, in the form of an increased mean maximal force‐generation capacity in cell‐transplanted muscles, compared to a sham‐injected control group. These studies highlight the potency of satellite cells to improve muscle function and the utility of the NSG‐mdx 4Cv model for studies on muscle regeneration and Duchenne muscular dystrophy therapy. STEM Cells 2013;31:1611–1620